Among greenery, water and architecture.: The landscape of the Aventine hill in the Baroque Age (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2025)
The Aventine Hill, located at the southern limit of the ancient urban fabric of Rome, close to the left bank of the Tiber, stands out both in the history and landscape of the city for its eminent position dominating the river and for its leafy character, that still survives today, despite an intense twentieth-century edification. Although having housed a populous neighborhood in Roman times, close to the port and merchant infrastructure, the Aventine Hill remained almost empty for a long period between thefall of the Roman Empire and the early twentieth century. A series of ancient plans and views testify to this image of the hill, based on an intimate relationship with the Tiber and the large vineyards and gardens, marked with ruins of the Roman era, amongwhich only the great ecclesiastical complexes of Santa Sabina stood out, of Saint Alexios, of Saint Prisca, and of the Priory of Malta, surrounded by lush vegetation facing the water. This paper briefly traces the historical-urban events of the hill using the graphic sources (engravings and paintings), focusing on the large conventual complexes that dominate the top of the hill, called «Aventinus Maior».